ANALISIS SISTEM ANTRIAN KERETA API DI STASIUN BESAR CIREBON DAN STASIUN CIREBON PRUJAKAN - Sugito, Sugito; Fauzia, Marissa (MEDIA STATISTIKA, 2009)
Queue system is a group of customer, service, and some rules to regulate arrival customers. Queue happened if a customers which need a serve more than service capacity. Phenomenon queue will find easily in public facility. One of is train  queue at Cirebon Main Train Station  and Cirebon Prujakan Train Station. Queue happened from train awaiting to be ridden away and from train which would to go to station, so that makes sometimes inappropriate arrival and departure the train of schedule resulting cumulative of train passenger candidate. To analyse  problems of train queue happened in station Cirebon can be applied the application of the queue theory. The steps must to do is by to create the examination where the queue happened. Based on those analysis can be known queue model and performance measure of queue system. And from data analysis can get two best kind of model for service system at Cirebon Main Train Station, that is (M/M/1):(GD/∞/∞) and (G/G/3):(GD/∞/∞). And two model service system at Cirebon Prujakan Train station, that is (M/G/2):(GD/∞/∞) and (M/G/1):(GD/∞/∞).   Keywords : Queue System, The Cirebon Station, Queue Model